Investigating the poetic view of music in Attar's poetry with emphasis on imaginary forms - Nadimi, Behrooz (2021)
Imaginations in poets' poetry are the achievement of a kind of experience and awareness that the poet gains from his surroundings. Attar is one of the great mystics and poets of the vast field of Persian literature. With his painful mysticism, he has led the lovers of the path of conduct through seven valleys. Basically, some mystics were closely acquainted with hearing and music, and Attar is one of the most prominent of them. The purpose of this study is to study the forms of imagination in musical applications - terms, words and instruments - Attar's poetry. Studies have shown that Attar has refined his mystical thinking by using the thoughtfulness of musical terms. In this research, the author has extracted verses in which musical terms and instruments have no musical purpose. But from the point of view of imagination and poetic point of view, it was important that it be studied.